Molecular classification and prognosis in younger adults with acute myeloid leukemia and intermediate‐risk cytogenetics treated or not by gemtuzumab ozogamycin: Final results of the GOELAMS/FILO acute myeloid leukemia 2006‐intermediate‐risk trial. (18th April 2021) - Bouvier, Anne; Hamel, Jean‐François; Delaunay, Jacques; Delabesse, Eric; Dumas, Pierre‐Yves; Ledoux, Marie‐Pierre; Peterlin, Pierre; Luquet, Isabelle; Roth Guepin, Gabrielle; Bulabois, Claude Eric; Gallego Hernanz, Maria Pilar; Guillerm, Gaëlle; et al.
Abstract: In this randomized phase 3 study, the FILO group tested whether the addition of 6 mg/m 2 of gemtuzumab ozogamycin (GO) to standard chemotherapy could improve outcome of younger patients with de novo acute myeloid leukemia (AML) and intermediate‐risk cytogenetics. GO arm was prematurely closed after 254 inclusions because of toxicity. A similar complete remission rate was observed in both arms. Neither event‐free survival nor overall survival were improved by GO in younger AML patients (<60 years) ineligible for allogeneic stem‐cell transplantation. ( P = .086; P = .149, respectively). Using unsupervised hierarchical clustering based on mutational analysis of seven genes ( NPM1, FLT3 ‐ITD, CEBPA, DNMT3A, IDH1, IDH2, and ASXL1 ), six clusters of patients with significant different outcome were identified. Five clusters were based on FLT3 ‐ITD, NPM1, and CEBPA mutations as well as epigenetic modifiers ( DNMT3A, IDH1/2, ASXL1 ), whereas the last cluster, representing 25% of patients, had no mutation and intermediate risk. One cluster isolated FLT3 ‐ITD mutations with higher allelic ratio and a very poor outcome. The addition of GO had no impact in these molecular clusters. Although not conclusive for GO impact in AML patients <60 years, this study provides a molecular classification that distinguishes six AML clusters influencing prognosis in younger AML patients with intermediate‐risk cytogenetic.